The Role of The Constitutional Court in Maintaining the Balance of Power in Indonesia - Dony Setyawan; Atma Suganda; Supaphorn Akkapin (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
The role of the Constitutional Court in maintaining the balance of power in Indonesia is crucial in ensuring the achievement of a democratic and fair system of government. As an institution mandated to safeguard the constitution, the Constitutional Court has the main function of conducting judicial reviews of laws that conflict with the 1945 Constitution, as well as overseeing general and regional elections. In addition, the Constitutional Court also acts as a protector of citizens' constitutional rights, ensuring that economic, social and cultural rights are respected and protected. Through its authority, the Constitutional Court plays an important role in maintaining the principle of checks and balances in Indonesia, preventing abuse of power, and strengthening the system of separation of powers between the executive, legislative and judicial branches. In this context, the Constitutional Court functions as an independent and objective constitutional watchdog institution, which is an important element in maintaining the stability and sustainability of democracy in Indonesia.